French Economics of Convention and Economic Sociology - S Jagd (Journal of Economic Sociology, 2010)
The French Economics of convention tradition has developed to be an influential research tradition situated in the area between economics and sociology. The aim of the paper is to explore some of the themes that may be common to economics of conventions and economic sociology by looking more closely into three recent texts from the economics of convention tradition discussing, in slightly different ways, differences and similarities between economics of convention and economic sociology. It is argued that André Orléan’s point that a common aim could be to ‘denaturalise’ the institutional foundation of markets and of money may be an occasion for economic sociology to focus even more on elaborating on the institutional void created by traditional economic theory. A second point is that economic sociology could benefit from the perspective of a plurality of forms of coordination involved in economic action.